A Historical Perspective on US Treasuries Risk Premia - DAVANNE, OLIVIER (Bankers, Markets & Investors, 2024)
The uncontrolled growth of US public debt is causing some anxiety among investors in US Treasuries. It is therefore useful to estimate the current risk premia embedded in the US yield curve and assess the extent to which investors are pricing in potential future financing difficulties for the US government. In this paper, we provide both a theoretical and empirical explanation of the factors driving the US Treasuries yield curve and how it is possible to extract what market participants are currently pricing in. It is widely acknowledged that expectations about future US monetary policy play a crucial role in this market. However, there is a notable underestimation — even within academic literature — of the symmetrical role played by expectations regarding future risk premia. Through our original modeling of the US Treasuries yield curve, we document the history of these expected risk premia. Our findings indicate that from 2000 to 2022, investors consistently underestimated the strength of demand for US Treasuries, which may explain the somewhat unusual behavior of this key market during that period. Since 2022, however, a new paradigm has emerged. Demand for longterm US treasuries has declined due to the resurgence of inflation, while debt issuance has surged, driven by substantial deficits and the Federal Reserve’s Quantitative Tightening policies. Consequently, risk premia have increased sharply. The future remains highly uncertain as lower inflation could once again bolster demand for US Treasuries while public debt is expected to continue its rapid expansion. In this volatile environment, our model will help investors manage their positions by enabling real-time comparisons between their own expectations and the actual market pricing.